Optimal Stock Portfolio Issuers of Building Construction Registered in LQ45 Based on the Markowitz Approach - Haryana, Rizky; Mulyana, Bambang (The Economics and Finance Letters, 2019)
Increased construction industry and accelerated infrastructure programs drive economic development globally and open opportunities for investors in the capital market. Rational investors will choose investments that provide maximum returns with certain risks, or otherwise certain returns with minimal risk, depending on individual investors’ preferences. To minimize risk, one of the methods used is to form a portfolio. The purpose of this study was to find out how to assess the optimal portfolio of shares for building construction companies using the Markowitz approach. The data in this study are secondary based on daily stock prices obtained from the IDX during the period February 2018 to July 2018. The research method used is descriptive, quantitative research. The number of samples used is four issuers, with saturated sampling techniques. The analytical tool used to assess the optimal portfolio is the Markowitz model, and its data is processed using Microsoft Excel. The results showed that an efficient two-share portfolio was found in the combination of ADHI and WIKA issuers, an efficient three-share portfolio was found in a combination of ADHI, WIKA and WSKT issuers, and four-share portfolio alternatives for optimal portfolios were formed by a combination of ADHI issuers, PTPP, WIKA, and WSKT, which together produce the lowest risk level.